2019
DOI: 10.1186/s12934-019-1085-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell factories converting lactate and acetate to butyrate: Clostridium butyricum and microbial communities from dark fermentation bioreactors

Abstract: BackgroundInteractions between microorganisms during specific steps of anaerobic digestion determine metabolic pathways in bioreactors and consequently the efficiency of fermentation processes. This study focuses on conversion of lactate and acetate to butyrate by bacteria of dark fermentation. The recently recognized flavin-based electron bifurcation as a mode of energy coupling by anaerobes increases our knowledge of anaerobic lactate oxidation and butyrate formation.ResultsMicrobial communities from dark fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
92
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 39 publications
18
92
4
1
Order By: Relevance
“…Our previous work demonstrated that dark fermentation microbial communities fed molasses under mesophilic conditions are able to convert lactate and acetate to butyrate in batch experiments [18]. Here we propose a logical continuation and extension of the previously published studies aimed at (i) recognition of biodiversity and dynamics of dark fermentation microbial communities able and unable to convert lactate and acetate to butyrate and (ii) de nition of the conditions for the process of transformation.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Our previous work demonstrated that dark fermentation microbial communities fed molasses under mesophilic conditions are able to convert lactate and acetate to butyrate in batch experiments [18]. Here we propose a logical continuation and extension of the previously published studies aimed at (i) recognition of biodiversity and dynamics of dark fermentation microbial communities able and unable to convert lactate and acetate to butyrate and (ii) de nition of the conditions for the process of transformation.…”
Section: Introductionsupporting
confidence: 52%
“…Cross-feeding of lactate was also observed in reduced microbial communities composed of two components: butyrateproducing Clostridium beijerinckii and lactate-producer Yokenella regensburgei [26]. Furthermore, pure cultures of Clostridium acetobutylicum [27], Butyribacterium methylotrophicum [28], Clostridium diolis [29], Clostridium buttyricum [18] and Clostridium tyrobutyricum [30,31] anaerobically grown in media with acetate and lactate as exclusive carbon sources produced carbon dioxide, hydrogen and butyrate.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Evidence for a molecular mechanism of conversion of lactate to acetate 76 was first demonstrated in the acetogenic model organism Acetobacterium woodii, where for 77 every molecules of lactate converted to acetate only 1.5 molecules of ATP were generated 78 (Weghoff et al, 2015). This mechanism, so-called electron confurcation, was suggested to be 79 wide spread in other anaerobic lactate utilizers and hypothesized to be present in intestinal 80 butyrogenic bacteria (Weghoff et al, 2015;Louis and Flint, 2017;Detman et al, 2019). 81 Therefore, using a proteogenomic approach we aimed to investigate whether intestinal bacteria 82 also employ this electron confurcation to convert lactate to butyrate with a focus on A.…”
Section: Introduction 47mentioning
confidence: 99%